The modern methods of teaching English to students ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
In many parts of the world, there is a growing interest in modern methods of teaching English to students, the question of how to do it - how the curriculum, subject, topic and methodology should differ from the previously developed familiar norms gives birth.